(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
Though the negative results of the UN report in December 2018, new statements for peace in Lybia were proposed in order to stop criminal escalation and secure the democratic development of the State. By the way, the level of instability and violence is worrying for international institutions.